Caracterização mineralógica e da fragmentação de tipologias de minério de ferro e sua liberação - França, José Raphael Olegário (2019)
In a mineral deposit, ore are known with variable characteristics, which affects the processing stages of the manufacturing in terms of their efficiency and productivity. The present work was designed to investigate the variability in comminution stage of different iron ore typologies from the Anglo American mine in Conceição do Mato Dentro CMD. For this purpose, the characterization of the mineralogy of the breakage and the liberation of the different samples were carried out using different analysis techniques and breakage tests. The results showed different behavior in the comminution of the studied ores and it depends on the size of the particles (crushing or milling). Hence, this behavior can change or invert. The presence of quartz in the saccharide form, grain size and the arrangement of main minerals of the ore were the most relevant characteristics which influence the differentiation and the comminution of the analyzed typologies. The presence of quartz in the saccharoidal form in levels close to the iron minerals was shown to be relevant on behavior of the breakage function. After breakage, the fragments will be preferentially in the ranges close to their grain size and practically liberated. The grain size, mainly for quartz, was the main characteristic for the grinding competence of the samples. Finally, the grain size and the shape of the arrangement among minerals were determinant for minerals liberation.